Lung Cancer Cells-Controlled Dkk-1 Production in Brain Metastatic Cascade Drive Microglia to Acquire a Pro-tumorigenic Phenotype - Gan, Dong-Xue; Wang, Yi-Bei; He, Ming-Yang; Chen, Zi-Yang; Qin, Xiao-Xue; Miao, Zi-Wei; Chen, Yu-Hua; Li, Bo (Frontiers in Cell and Developmental Biology, 2020)
Objectives: Organotropism is primarily determined by tumor-derived exosomes. To date, the role of lung cancer cells-derived exosomes underlying the pre-metastatic niche formation is unclear. Materials and methods: The animal models of retro-orbital and intra-ventricular injection were constructed to administrate lung cancer cell-derived exosomes. Cytokine array was used to screen the cytokines released from brain endothelium after internalization of lung cancer cells-derived exosomes. The cellular co-culture system was established to mimic microglia-vascular niche contained lung cancer cells-derived exosomes. The levels of Dkk-1 and the activities of microglia were analyzed by qRT-PCR, western blot and immunofluorescence. In vivo selections of highly brain metastatic cells were performed to analyze the direct interaction of lung cancer cells with microglia. Results: Animal studies demonstrated that there was a suppressive signal transferred from brain endothelium to microglia after internalization of lung cancer cells-derived exosomes into brain endothelium, which caused an absolutely less M1 phenotypic microglia and a relatively more M2 phenotypic microglia. Further results indicated that lung cancer cells-derived exosomes induced a release of endogenous Dkk-1 from brain endothelium, which rendered microglia to acquire a pro-tumorigenic feature in pre-metastatic niche. Subsequently, the declines of Dkk-1 in metastatic lung cancer cells removed the suppression on microglia and enhanced microglial activation in metastatic niche. Conclusion: Our findings shed a new light on the synergistic reaction of the different cells in “neurovascular units” towards the metastatic messages from lung cancer cells and provided a potential therapeutic pathway for lung cancer metastasis to brain.